1985
DOI: 10.1139/z85-227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on larval tolerance and early developmental rates of four species of echinoderms

Abstract: Larval tolerances and developmental rates of four species and one hybrid cross of echinoderms were determined as a function of salinity. Fertilization and development of Strongylocentrotus droebachiensis (O.F. Muller, 1776), Strongylocentrotus purpuratus (Stimpson, 1857), Strongylocentrotus pallidus (G.O. Sars, 1871), and Pisaster ochraceus (Brandt, 1835) larvae were observed. A hybrid was created by fertilizing eggs of S. droebachiensis with sperm from S. pallidus. Fertilized eggs were placed in filtered, nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 17 publications
0
17
1
Order By: Relevance
“…Although we did not rear our cultures to the larval stage, delayed hatching in COTS due to low salinity is likely to be associated with larval abnormality, as shown for Pisaster ochraceus and Echinaster sp. [49,53]. Despite our finding of delayed hatching of COTS, no signs of changes in stage at hatching were observed, as has been found in some echinoids [29].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Although we did not rear our cultures to the larval stage, delayed hatching in COTS due to low salinity is likely to be associated with larval abnormality, as shown for Pisaster ochraceus and Echinaster sp. [49,53]. Despite our finding of delayed hatching of COTS, no signs of changes in stage at hatching were observed, as has been found in some echinoids [29].…”
Section: Discussioncontrasting
confidence: 63%
“…In general, decreased salinity is well known to delay or retard development in echinoderms [26,28,29,45,47,[49][50][51][52]. For COTS, hatching was significantly delayed in embryos reared from fertilization at 27 ppt.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have demonstrated that S. droebachiensis is one of the most tolerant echinoderms to hyposalinity (Russell 2013). Roller and Stickle (1985) showed that in the Pacific, larvae of S. pallidus failed to develop, and cultures experienced 100% mortality at salinities below 27.5‰. In contrast, although cultures of S. droebachiensis developed slowly at salinities ≤22.5‰ and below, survival was 100% at salinities as low as 20‰.…”
Section: Addison and Kimmentioning
confidence: 99%
“…Based on the results of hybridation experiments between two morphs of Echinaster modestus, Watts et al (1982) drew the conclusion that varying thermosaline requirements are genetically controlled and not environmentally influenced; similar results were obtained by Roller & Stickle (1985) by means of hybrid-cross experiments between two species of Strongylocentrotus. Our data agree with the latter conclusions.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies demonstrate that earlier embryonic stages are more sensitive than adults to these abiotic factors (Runnstrom, 1927;L/3nning, 1959;Calabrese, 1969;Gorodilov, 1969;Roller & Stickle, 1985, 1993. Furthermore, the tolerance limits of embryos are probably responsible for the relatively fixed thermo-saline range of reproduction (Andronikov, 1975;Fujisawa, 1989).…”
Section: Introductionmentioning
confidence: 99%